INTEGRATED INTER-AGENCY COORDINATION FOR EFFECTIVE DISASTER MANAGEMENT IN KLANG VALLEY - Nadhirah Nordin; Khairul Nizam Taib; Mohd Haniff Sofian; Suzana Ali Hassan; Noor Azmi Mohd Zainol (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Disaster management in Klang Valley, Malaysia, requires robust inter-agency coordination to effectively handle natural disaster such as landslides and floods. This study explores the enhancement of integrated inter-agency coordination for effective disaster management in Klang Valley through a qualitative approach involving in-depth interviews, observations, and literature review. The findings highlight several key areas for improvement; 1) enhancing communication infrastructure by upgrading the Government Integrated Radio Network (GIRN) for extensive coverage, 2) establishing a centralized communication hub, and leveraging robust, independent communication systems to ensure continuous information flow during disasters, 3)Regular joint training exercises and tailored programs for District Officers are recommended to improve preparedness and operational readiness, 4) clear policies and Standard Operating Procedures (SOPs) defining the roles and responsibilities of each agency, 5)strengthening coordination with non-governmental organizations (NGOs) through formal mechanisms and regular meetings is crucial to ensure consistent and fair aid distribution, 6)enhancing community awareness and preparedness via regular programs and developing community-based response plans in collaboration with local authorities can further improve disaster management outcomes.